2016
DOI: 10.3390/molecules21101376
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of an Isolable Dialkylsilylene with Aroyl Chlorides. A New Route to Aroylsilanes

Abstract: Abstract:The reactions of isolable dialkylsilylene 1 with aromatic acyl chlorides afforded aroylsilanes 3a-3c exclusively. Aroylsilanes 3a-3c were characterized by 1 H-, 13 C-, and 29 Si-NMR spectroscopy, high-resolution mass spectrometry (HRMS), and single-crystal molecular structure analysis. The reaction mechanisms are discussed in comparison with related reaction of 1 with chloroalkanes and chlorosilanes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…The distance of the Sn(1)–Cl(1) (2.394(2) Å) bond is longer than that of chloro­(triphenyl)­tin (2.35 Å), but shorter than those of trialkyl derivatives such as Cy 3 SnCl (2.4558 Å, Cy = cyclohexyl) and Me 3 SnCl (2.43 Å) . The C(17)O(1) bond distance of 1.192(7) Å is significantly shorter than those of the corresponding acyl­(chloro)­silanes ( D , 1.217–1.223 Å) …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The distance of the Sn(1)–Cl(1) (2.394(2) Å) bond is longer than that of chloro­(triphenyl)­tin (2.35 Å), but shorter than those of trialkyl derivatives such as Cy 3 SnCl (2.4558 Å, Cy = cyclohexyl) and Me 3 SnCl (2.43 Å) . The C(17)O(1) bond distance of 1.192(7) Å is significantly shorter than those of the corresponding acyl­(chloro)­silanes ( D , 1.217–1.223 Å) …”
Section: Resultsmentioning
confidence: 96%
“…We have recently reported a similar insertion of an isolable dialkylsilylene as a conventional synthetic method for the corresponding acyl­(chloro)­silanes D (Chart ). During the course of our studies of the reactions of isolable dialkylstannylene 1 (Chart ) with various functional groups, we have found that the stannylene inserts exclusively into the C–Cl bonds of acyl chlorides, providing a number of acyl­(chloro)­stannanes that are difficult to synthesize via conventional methods. They are expected to be more reactive than the corresponding acylsilanes and to serve as better synthetic reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Acyl chlorides were also used as a chloride source to react with germylene and stannylenes, in which the corresponding acylgermanes and acylstannanes have been obtained undergoing an insertion of acyl-Cl bond. [50][51][52] While the reaction of 3a with acetyl chloride 8 was carried out at ambient temperature giving the chlorogoldgermane 9 in 67% together with acetyl(triemethylphosphine)gold (Fig. 7a).…”
Section: Full Textmentioning
confidence: 99%
“…In 2016, Kira's group reported the synthesis of acylsilanes by the reaction of dialkylsilylene with benzoyl and aromatic acyl chloride (Scheme 24). [35] During the stipulated mechanism, the reactions started from the formation of acylsilane-silylene complex followed by the formation of a three-membered ring transition state through the concerted mechanism to generate the acylsilanes. Alternatively, silylene played a vital role as a Lewis acid to activate the CÀ Cl bond after the formation of acylsilane-silylene complex to access to the thermally stable acylsilanes in high yields.…”
Section: The Silylation Of Carboxylic Acids or Carboxylic Acid Derivamentioning
confidence: 99%
“…In 2016, Kira's group reported the synthesis of acylsilanes by the reaction of dialkylsilylene with benzoyl and aromatic acyl chloride (Scheme ) . During the stipulated mechanism, the reactions started from the formation of acylsilane‐silylene complex followed by the formation of a three‐membered ring transition state through the concerted mechanism to generate the acylsilanes.…”
Section: The Synthesis Of Acylsilanesmentioning
confidence: 99%